Divided-difference equation and three-term recurrence relations of some systems of bivariate q-orthogonal polynomials. Issue 12 (2nd December 2017) - Tcheutia, D. D.; Foupouagnigni, M.; Guemo Tefo, Y.; Area, I.
Abstract: Partial divided-difference equations and three-term recurrence relations satisfied by the bivariate Askey–Wilson and the bivariate q -Racah polynomials are computed in this work. By using limiting processes, partial divided (or q )-difference equations and three-term recurrence relations are also provided for each of the following families of orthogonal polynomials: the bivariate continuous dual q -Hahn, the bivariate Al-Salam-Chihara, the bivariate continuous q -Hahn, the bivariate q -Hahn, the bivariate dual q -Hahn, the bivariate q -Krawtchouk, the bivariate q -Meixner, and the bivariate q -Charlier polynomials.